Att älska sitt jobb: Om passion, entusiasm och brist på företagsanda - Petersson McIntyre, Magdalena (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2015)
This article focuses on labour processes among workers in retail in Sweden. It is a study of the commodification of body and affect in a field organized around commercial exchange and builds on participant observations in stores and thirty interviews with workers in different fields of retail (fashion, perfume, home electronic and diy-stores). Retailing is a part of the service economy that is signified by short-term employments and precarity on the one hand and on the other hand of a high degree of demands on skills that involve and commodify the bodies, dispositions and emotions of the individual workers. The article discusses why so many working as sales staff in retailing say that they love their job and why “passion” is considered so important. During the interviews and observations it was striking how the workers identified strongly with their employers. Words such as “natural”, “obvious” and “taken for granted” were very often used to describe why work was organized the way it was. Workers’ attitudes are examined as a result of the development on the labour market in the last decades and as an affective identification with relations on the neoliberal work market.